A stylometric investigation across genders and individual authors based on a specialized Vietnamese corpus - Nguyen, Nhung; Dinh, Dien (Advances in Social Sciences Research Journal, 2021)
Recently, there has been renewed interest in stylometry, a branch of forensic linguistics evaluating linguistic features which affect an author’s writing style. However, no known empirical research has attempted to explore relationships between word-level features in Vietnamese texts and writing style, both across genders and individual authors. Using two series of correspondence analysis, the current study thus seeks to analyze the most significant linguistic features across genders and individual authors based on a rich-annotated specialized Vietnamese corpus. In terms of genders, the most significant associations on writing style were identified for the combination of personal pronouns and negative words, whereas the seperated feature sets have less discriminating ability. For individual authors, negation words demonstrate their significant associations, and personal pronouns again have insignificant relationships with individual writing style. As a result of these investigations, suggestions were identified for future research.